(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
This study aims to determine the diversity of butterflies in protected forest of Pulau Panas Village, Tanjung Sakti Pumi, Lahat, South Sumatra. The research was conducted in October â€“ November 2020. The research sites were three different types of habitat, namely primary forest, riverbanks, and transitional or ecotone area of forests and plantations. Data collection uses exploration or roaming techniques following a 300-meter-long path with a width of 2 m to the right and 2 m to left in each habitat type using insect nets. The results obtained 61 species of butterflies (Lepidoptera: Rhopalocera) belonging to 5 families (8 species of Papilionidae, 11 species of Pieridae, 33 species of Nymphalidae, 3 species of Hesperiidae and 6 species of Lycaenidae). The highest diversity (Shannon index) is in primary forest habitat with H’= 3.67; followed by transitiononal forest and plantation areas with H’ = 3.62, while the lowest diversity index is riverbanks with H’= 3.24. The evennes index of the species is almost the same (E>0.9). The highest species richness was found in primary forest (Dmg: 9.75). Protected butterfly species (according to the Decree of Ministry of Environment and Forestry No. 106 year 2018) found in this study is Troides helena. Keywords: diversity, lepidoptera, protected forest, rhopalocera, south sumatra